Pengaruh Pemahaman Wajib Pajak dan peranan Aparat peryajakan terhadap Kepatuhan wajib Pajak Bumi dan Bangunan di Kota surakarta - Magdalena Nany; Endang Satyawati; Ferani Ferani (Jurnal Riset Akuntansi dan Keuangan, 2010)
The objective of this research was to give empirical evidence about the fficts of tax payer's lmowledge and tax fficer's rolq on rand and building tar payer's compliance partially. This research was also intended to give empirical evidence obout the effects of tax payerzs knowledge and tax fficer,s roles onland and building tax payer's compliance simultaneously. Data takenfrom 150 respondents were analyzed by multiple regression analysis. The results show that ta'r payer's lonwledge and tax officer's roles partially had significant fficlon land and building tax payer's compliance. The results also show that tax payer's lvtowledge and tav fficer's roles simultaneously had significant ffict. on land and building tax payer's compliance.Keywords : tax payer's lmowledge, tax fficer's roles, tax payer's compliance, land and building tar